Coastal marine heatwaves in the Santa Barbara Channel: decadal trends and ecological implications - Chan, Kit Yu Karen; Kui, Li; McDonald, Adriane M.; Ritger, Amelia L.; Hofmann, Gretchen E. (Frontiers in Marine Science, 2024)
Marine heatwaves (MHWs) are of increasing concern due to the emerging ecological and socioeconomic impacts on coastal ecosystems. Leveraging the data of the Santa Barbara Coastal Long-Term Ecological Research project, we analyzed the MHW event metrics observed in the kelp forest ecosystem and across Santa Barbara Channel, CA, USA. Not only was there a significant positive trend in the number of MHWs recorded, their duration and intensity were also increasing over time. MHWs were detected year-round, suggesting that marine organisms have exposure risks regardless of their phenology. Exposure at one life history stage could have a legacy effect on the subsequent, implying little temporal refuge. In contrast, the coastal moorings data revealed that nearsurface and bottom events were not necessarily coupled even at less than 15 m. Such spatial variation in MHWs might provide temporary refuge for mobile species. These observations also highlight the importance of depth-stratified, long-term coastal monitoring to understand spatial-temporal variation in MHW stress on coastal communities.